1998
DOI: 10.1007/s004320050157
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment serum lactate dehydrogenase as additional staging parameter in patients with small-cell lung carcinoma

Abstract: These results suggest that pretreatment LDH may be used as an additional staging parameter in SCLC, which can identify prognostic subgroups before treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Previous studies have reported that PS score, disease extent, LDH level, CEA and NSE significantly correlates with overall survival benefit in patients with SCLC8242526. These findings are consistent with the results of our studies, which demonstrated that better PS, limited staging, and normal serum levels of LDH were significantly associated with a longer survival than those with patients with a poor PS, extensive staging, and elevated serum LDH levels (Table 1).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previous studies have reported that PS score, disease extent, LDH level, CEA and NSE significantly correlates with overall survival benefit in patients with SCLC8242526. These findings are consistent with the results of our studies, which demonstrated that better PS, limited staging, and normal serum levels of LDH were significantly associated with a longer survival than those with patients with a poor PS, extensive staging, and elevated serum LDH levels (Table 1).…”
Section: Discussionsupporting
confidence: 92%
“…These prognostic markers are associated with overall survival (OS) in SCLC8910. Of the prognostic factors, PS and disease stage are important prognostic indicators for SCLC1112.…”
mentioning
confidence: 99%
“…We have found that elevated LDH was an independent poor prognostic factor for survival, as was found in other studies [2,7,8,10,12,13]. Elevated LDH levels may reflect occult disease which cannot be detected with current imaging techniques, tumor burden, metabolic activity of malignancy, or increased risk of tumor recurrence [13]. Serum LDH is also known to play an important role in the prediction of the metastatic pattern.…”
Section: Discussionmentioning
confidence: 75%
“…Under these conditions, tumor cells characteristically show rapid anaerobic glycolysis,23 a process in which LDH plays a central role 24. Not surprisingly, then, various malignant tumors have been reported to express higher levels of LDH isoforms than healthy cells, and S-LDH levels in these patients are higher than in healthy controls 9,10,25. The elevated S-LDH may reflect, at least in part, release of the enzyme from malignant cells 16,26.…”
Section: Discussionmentioning
confidence: 99%